O processo de inovação de produtos da Electrolux como modelo de Empreendedorismo Corporativo - Mansur, Elias Mendonça (2010)
The Corporate Entrepreneurship is a topic that has recently attracted great interest from the academy, but few studies relate it under the theoretical point of view, the innovation process in organizations. This fertile field of study was the opportunity to contribute, even in simple way, to enrich the topic. This present research, through a case study, sought to empirically verify the extent to which the innovation process of products from Electrolux, unit Floor Care and Small Appliances, can be considered as a model or source of corporate entrepreneurship. Feauteres of Corporate Entrepreneurship present in a innovation process were collected and defined by reviewing bibliographies of current literature. Characteristics of Corporate Entrepreneurship present in innovation process were collected and defined by reviewing bibliographies of current literature. Sought to deepen through the verification of new features collected in the case study. Divided qualitative, with semistructured interviews and quantitative part, with questionnaires to all involved either directly in the process, this project can refute, validate and search features presented and not presented in the literature, evaluating the model of study as a model of Corporate Entrepreneurship and thereby opening the opportunity for future exploration.